Tourism as a source of taxation – the Portuguese case - Rodrigues, Carlos (2020)
This research analyzes the financial contribution generated by the activity of tourism to the general budget of the state of Portugal through the taxes collected on the profits of companies linked to tourism and on VAT that tourists pay in Portugal. We concluded, in the end, that the financial values generated for the state budget are of great importance and have been growing.